Applications of Ammonium Bifluoride in Organic Synthesis - Li, Jia-Sheng; Dong, Wei-Zhe; Lu, Hui; Zhang, Fu-Min (Current Organic Chemistry, 2018)
Background: Ammonium bifluoride is a reagent widely used in organic synthesis; however, the systematic collection and classification have not been covered until now. Methodology: In this review, we aim to systematically summarize the application of ammonium bifluoride in organic synthesis. Conclusion: It can be used for deprotection of hydroxyl protected groups (esp. Silyl protection). It is also used for introducing F & N atoms into organic molecules; promoting cyclization reactions acting as a multifunctional reagent.
Keywords: removal of hydroxyl protecting groups